Kinetics of acetylcholinesterase inhibition by an aqueous extract of Cuminum cyminum seeds. - Kumar, Suresh; Chowdhury, Suman (International Journal of Applied Sciences and Biotechnology, 2014)
The cholinergic hypothesis of Alzheimer’s disease (AD) has provided the rationale for the current pharmacotherapy of this disease. Acetylcholinesterase (AChE) inhibitors are currently the only approved therapy for the symptomatic treatment of AD. The current drugs available in the market has shown various side effect which prompted scientist to search for new and potent AChE inhibitors which exerts minimal side effect in AD patient. In present study, an aqueous extract of Cumin cyminum was tested for in vitro acetylcholinesterase inhibitory activity based on Ellman’s method. C. cyminum showed maximum inhibition of 76.90±0.003% in an aqueous extract at 50μg/ml final concentration. Further studies were conducted to elucidate the mode of AChE inhibition by kinetic studies. Competitive inhibition was observed at lower concentrations (12.5μg/ml & 25μg/ml) and mixed inhibition was observed at higher concentrations (50μg/ml & 100μg/ml). DOI: http://dx.doi.org/10.3126/ijasbt.v2i1.9348 Int J Appl Sci Biotechnol, Vol 2(1): 64-68